Letter to the Editor: License Portability for Occupational Audiologists is Essential - George R. Cook (International Journal of Telerehabilitation)
Occupational audiologists have a crisis in their profession and need advocates. These audiologists are primarily responsible for industrial hearing conservation programs and their compliance with multiple regulations, such as Occupational Safety and Health Administration (OSHA), Mine Safety and Health Administration (MSHA) and the Federal Railroad Administration.  Occupational hearing programs, for the most part, are multi-state programs as companies and corporations are national organizations. Also, companies may contract services across state lines as local services may not be desired or available. Individual state telepractice regulations require audiologists who are professionally supervising these programs via the internet and phone, to secure licensure in each state. For this licensure redundancy, the cost in time and tracking are enormous.  It is imperative that the American Speech-Language-Hearing Association (ASHA), secure multistate licensure for speech-language pathologists and audiologists. For the profession of occupational audiology, it is essential.